2012
DOI: 10.7150/ijbs.4047
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Allele of Human MRC1 Confer Protection against Tuberculosis in a Chinese Population

Abstract: Mannose receptor is a member of the C-type lectin receptor family involved in pathogen molecular-pattern recognition, and plays a critical role in shaping host immune response. Single nucleotide polymorphisms (SNPs) in the MRC1 gene may affect expression levels and differences in the structure and function of proteins in different individuals, thereby affecting individual susceptibility to pulmonary tuberculosis. However, to date, MRC1 polymorphisms associated with susceptibility to pulmonary tuberculosis have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
1
31
1
3
Order By: Relevance
“…Needleless to say PCR has been used in host defense research and it provided valuable information in various disease settings including cirrhosis. 16,17,39,40 For instance, in a recent study the investigators demonstrated molecular evidence of bacterial antigenic material in cirrhotic ascites in the absence of a microbiological evidence for SBP. 40 MR studies, in particular, identified an association between polymorphic allele of MRC1 and susceptibility to certain infections including tuberculosis and leprosy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Needleless to say PCR has been used in host defense research and it provided valuable information in various disease settings including cirrhosis. 16,17,39,40 For instance, in a recent study the investigators demonstrated molecular evidence of bacterial antigenic material in cirrhotic ascites in the absence of a microbiological evidence for SBP. 40 MR studies, in particular, identified an association between polymorphic allele of MRC1 and susceptibility to certain infections including tuberculosis and leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…40 MR studies, in particular, identified an association between polymorphic allele of MRC1 and susceptibility to certain infections including tuberculosis and leprosy. 16,17 In those studies standard PCR technique was used. This study has tested the gene encoding MR and in all patients' samples we were unable to visualize a band representative of MRC1on agarose gel electrophoresis (Figure 4a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations